The Identification of Complain Responding Turn in `Shopaholic to the Rescue` - Setia Adi Nugraha; M. R. Nababan; Djatmika Djatmika (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
The purpose of this research to identify types of turn which respond to complaining speech act in Shopaholic to the Rescue novel and use pragmatics approach. It is because in pragmatics field, moreover in conversation turn becomes one of important foundations in reaching the purpose of communication, especially in verbal communication. Besides when people want to have a conversation and being involved in it, it must be organized, managed, and it can be seen by the turn. This research is categorized as a descriptive-qualitative research with embedded case study and using pragmatics approach. The data of this research are taken from conversations between characters in the Shopaholic to the Rescue novel which contain turns that respond to complaining speech act, and this study only takes verbal responds. As the result of this research, there are 45 types of complain responding turn from 120 data. Stating becomes the most dominant turn in responding the complaining speech act with 14 data, followed by complaining (11 data), asking (9 data), and explaining (9 data).